LITERARY QUEST AS A TOOL FOR FORMING READING INTERESTS IN PRIMARY SCHOOL CHILDREN - Blahun, Nataliia; Dovbenko, Svitlana; Piatka, Nadiia (Mountain School of Ukrainian Carpaty, 2022)
The use of innovative forms in the lessons of the Ukrainian language and literature increases students' interest in the subject content, and improve the quality of education. A modern teacher should organize a lesson in a way that children always obtain a desire to learn new things. Game educational technologies, especially quests, are the crucial part of these problems. The purpose of the study is to analyze and highlight the features of using a literary quest as an instrument of forming reading interests in the primary school. Quest is an interactive game technology that comprise story, adventure, goal-oriented and team-based character, which allows students to better learn the educational material, obtain knowledge while performing tasks, reveal certain qualities (leadership, intelligence, benevolence) and, most importantly, evokes a lot of positive emotions in players and memories. Teachers can easily use this innovative technology in literature lessons, during which reading competence is formed and developed, also speech, literary and intellectual development takes place. This will open opportunities for children to independent creative activity, teaches to perceive, analyze, and understand what is read. Literary quests are personalized lessons in the study of literature that teach independence, creativity and, most importantly, form reading interests in primary school. The use of quest technologies has a positive effect on the skills of interpreting works of art: pupils develop the skills of social behavior, study collective work in teams, and involvement in real practical activities expands the creative environment for cognitive activity. The game quest will allow students to develop their communication skills while working in a team and deepen their knowledge while mastering the educational material.